Pengaruh Model Quantum Teaching Berbantuan Media Audio Visual terhadap Hasil Belajar PAI SMP Negeri 3 Bukitinggi - Wellistya Ayu Ningsih; Wedra Aprison (Lembaga Yasin AlSys, 2026)
Learning outcomes in Islamic Religious Education (PAI) have received considerable attention in various studies, but research specifically integrating the Quantum Teaching model supported by audiovisual media into PAI learning at the junior high school level remains limited. This study aimed to analyze the effect of the Quantum Teaching model supported by audiovisual media on the PAI learning outcomes of seventh-grade students at SMP Negeri 3 Bukittinggi. The study employed a quantitative approach with a quasi-experimental, posttest-only control group design involving 63 students, comprising 32 students in the experimental class and 31 students in the control class selected through purposive sampling. Data were collected using a learning outcomes test that met the validity and reliability criteria and were subsequently analyzed using descriptive statistics, a normality test, a homogeneity test, an independent-samples t-test, and one-way analysis of variance with the assistance of IBM SPSS Statistics 26. The results showed that the mean learning outcome score of students in the experimental class was 84.22, which was higher than that of the control class at 68.71. Hypothesis testing yielded a significance value of 0.000 < 0.05, indicating that the Quantum Teaching model supported by audiovisual media had a significant effect on PAI learning outcomes. These findings confirm that active and interactive learning supported by audiovisual media can improve students’ learning outcomes. Theoretically, this study strengthens the application of Quantum Teaching theory and the Cognitive Theory of Multimedia Learning in PAI learning, while practically, the results can serve as a reference for teachers and schools in developing more innovative and effective PAI learning strategies.